2021
DOI: 10.3390/ma14174919
|View full text |Cite
|
Sign up to set email alerts
|

Printable and Machinable Dental Restorative Composites for CAD/CAM Application—Comparison of Mechanical Properties, Fractographic, Texture and Fractal Dimension Analysis

Abstract: Thanks to the continuous development of light-curing resin composites it is now possible to print permanent single-tooth restorations. The purpose of this study was to compare resin composites for milling -Gandio Blocks(GR), Brilliant Crios(CR) and Enamic(EN) with resin composite for 3D printing—VarseoSmileCrown plus(VSC). Three-point bending was used to measure flexural strength (σf) and flexural modulus (Ef). The microhardness was measured using a Vickers method, while fractographic, microstructural, texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 44 publications
(60 reference statements)
3
59
1
2
Order By: Relevance
“…A weak correlation (r = 0.16) between the FD in the 100 µm × 100 µm scale and the Sa parameter was observed, and the r parameter was significantly lower (r = −0.06) for the scale 5 µm × 5 µm. Examination of the correlation between the FD and the physical properties of the material is useful; this was confirmed by Grzebieluch et al who revealed a strong positive correlation between the FD of composite dental materials and the flexural module [14].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A weak correlation (r = 0.16) between the FD in the 100 µm × 100 µm scale and the Sa parameter was observed, and the r parameter was significantly lower (r = −0.06) for the scale 5 µm × 5 µm. Examination of the correlation between the FD and the physical properties of the material is useful; this was confirmed by Grzebieluch et al who revealed a strong positive correlation between the FD of composite dental materials and the flexural module [14].…”
Section: Discussionmentioning
confidence: 85%
“…This algorithm allows us to analyze 8-bit monochromatic images. It was fully described in our previous study [14]. In this method, the analyzed image is divided into boxes such as in scale ε.…”
Section: Fractal Dimension Analysismentioning
confidence: 99%
“…VS showed an increase in fracture toughness and bond strength after 6 months of aging and then a slight decrease compared to the control at 12 months. The cause of this phenomenon is probably the heating phase of the aging process facilitating additional polymerisation of the free monomer in the composites at the bond interface [30,31]. The VP group with the lower viscosity composite would have had a higher amount of free monomer and resin available for contact with the bond surface than the more viscous F composite which has a higher percentage filler content and therefore less resin available for contact at the VF bond interface.…”
Section: Discussionmentioning
confidence: 99%
“…FD analysis can be applied in the description of irregular or complex surfaces or shapes. Fractal dimension analysis (FDA) has been reported in surface testing of various dental materials; among them are xenogeneic bone substitutes, lithium disilicate-based crowns, zirconia dental implants, dental restorative composite, or orthodontic wires [ 6 , 7 , 8 , 9 ]. Since the fractal architecture concept is particularly interesting in surface and materials science, it also can be adapted to assess the surface of titanium dental implants.…”
Section: Introductionmentioning
confidence: 99%